SCREENING OF COMPETENT RICE ROOT ENDOPHYTIC BACTERIA TO PROMOTE RICE GROWTH AND BACTERIAL LEAF BLIGHT DISEASE CONTROL - Prihatiningsih, Nur; Adi Djatmiko, Heru; Lestari, Puji (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Screening of competent rice root endophytic bacteria to promote rice growth and bacterial leaf blight disease control. This study was aimed to collect isolate endophytic bacterial of rice roots which able to produce IAA, determine the effect of endophytic bacteria application in stimulating rice plant growth, andÃ‚Â  evaluate the potential of rice root endophytic bacteria for controlling bacterial leaf blight. This reasearch was carried out at the Screen House, Plant Protection Laboratory, and Agrohorti Laboratory of the Agriculture Faculty, Jenderal Soedirman University. Isolation of rice root endophytic bacteria was carried out by purposive random sampling from several marginal lands. The results showed that 8 isolates of rice root endophytic bacteria were able to produce IAA, ranging from 57.56 to 79.33 ppm and B07 isolate from Serayu produced the highest amount of IAA. The B04 and B07 isolates were contributed to increase the rice plant growth. The application of rice root endophytic bacteria was effective in controlling bacterial leaf blight.